Novel DC-biasing circuits with arbitrary harmonics-control capability for compact high-efficiency power amplifiers. Issue 7 (22nd April 2019) - Tanaka, Shinichi; Oda, Tomoya; Saiki, Kento
Abstract: The next generation mobile communication systems impose challenging performance, size, and cost requirements on the power amplifiers (PAs). This paper presents novel DC-biasing circuits, which are compact and yet can control the harmonics almost arbitrarily. The proposed circuit consists of a composite right-/left-handed (CRLH) transmission line (TL) stub, of which the size and harmonics-control function can be tuned by modifying the dispersion diagram of the stub line. As a proof of concept, a compact 2-GHz 7-W GaN HEMT class-F PA using the versatile CRLH-TL stubs was fabricated, demonstrating 85.8% drain efficiency and 77.3% power-added efficiency.